Sistem Informasi Geografis Persebaran Sepeda Motor Dan Tingkat Kecelakaan Di Jawa Tengah Berbasis Web - Baromim Triwijaya; Bambang Agus Herlambang; Ahmad Khoirul Anam (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Population growth in Central Java is increasing motorbike ownership, causing traffic problems, air pollution and accidents. The lack of an integrated information system regarding the relationship between the number of motorbikes and accident rates is a major obstacle. This research applies a Geographic Information System (GIS) with the Waterfall system development method. The result is a web-based GIS implementation that maps the number of motorbikes and accident rates in one interactive map. This GIS is expected to overcome limitations in access to accurate data and provide an in-depth view of the impact of the number of motorbikes on traffic accidents in the region. This research is an important basis for decision making and policy design to improve traffic safety in Central Java